2018
DOI: 10.7555/jbr.31.20160120
|View full text |Cite
|
Sign up to set email alerts
|

Dietary crocin reverses melanoma metastasis

Abstract: Crocus sativus and its bioactive constituent crocin are well known for anti-tumor potential in different models. However, the efficacy of crocin on in-vivo melanoma metastasis is not yet reported. In this study, melanoma metastatic model was developed by tail vein injection of B16F-10 cells in to C57BL/6 mice. Metastatic mice treated with two different doses of crocin (250 and 500 µg/kg of bodyweight) for 10 days and parameters such as lung metastasis inhibition, mean survival time, lung hydroxyproline, uronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Metastasis and EMT are closely related to the poor prognosis of patients with gastric cancer (Cui et al, ; Zhou et al, ). Bakshi, Hakkim, Sam, Javid, and Rashan () demonstrated that dietary crocin reversed melanoma metastasis in a mouse model. Crocin also showed antimetastatic effects in 4T1 breast cancer cells through interference with the Wnt/β‐catenin pathway (Arzi, Riazi, Sadeghizadeh, Hoshyar, & Jafarzadeh, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis and EMT are closely related to the poor prognosis of patients with gastric cancer (Cui et al, ; Zhou et al, ). Bakshi, Hakkim, Sam, Javid, and Rashan () demonstrated that dietary crocin reversed melanoma metastasis in a mouse model. Crocin also showed antimetastatic effects in 4T1 breast cancer cells through interference with the Wnt/β‐catenin pathway (Arzi, Riazi, Sadeghizadeh, Hoshyar, & Jafarzadeh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis and EMT are closely related to the poor prognosis of patients with gastric cancer (Cui et al, 2018;Zhou et al, 2017). Bakshi, Hakkim, Sam, Javid, and Rashan (2017) demonstrated that dietary crocin reversed melanoma metastasis in a mouse model.…”
Section: Crocin Modulates Klf5 Expression By Elevating Mir-320 Expres...mentioning
confidence: 99%
“…According to research, crocin is a compound with high antioxidant and anti-inflammatory properties that, due to its positive properties, can reduce the production of free radicals and greatly protects the cells and tissues involved (Bakshi et al, 2017). So, since the phenomenon of apoptosis abolished many in cancer cells, the use of crocin is likely to induce the apoptotic process to cause premature death of cancer cells (Hoshyar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most herbal research today relates to the healing and therapeutic effects of traditional herbs that have long been used in societies. One of these plants, which has multiple scientific articles on its properties and importance in published scientific journals, is the saffron plant from the Iridaceae family with various compounds and antioxidant properties, one of the compounds of interest to researchers in saffron is crocin (Bakshi et al, 2017). Crocin is a carotenoid chemical compound with very high antioxidant properties (Bakshi et al, 2017) and has anti-inflammatory properties (Bakhtiary et al, 2014;Bakshi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…matrix metalloproteinase (MMP) 9 is a matrix protein associated with extracellular matrix (ECM) remodeling that promotes tumor progression and regulates the activity of cell adhesion molecules and cytokines ( Joseph et al, 2020 ). Bakshi et al (2017b) found that crocin inhibited the expression of MMP-2, MMP-9, ERK-2, K-ras and VEGF, and attenuated the ability of melanoma cells (B16F-10) to invade, migrate, and adhere by upregulating the expression of E-cadherin. Human gastric mucosal epithelial cells (GES-1) have malignant cell characteristics such as proliferation, apoptosis, and metastatic ability.…”
Section: Inhibition Of Tumor Cell Metastasis and Invasionmentioning
confidence: 97%